Cardiac evaluation after experimental intoxication by Amorimia rigida (Malpighiaceae) extracts in rabbits - Borboleta,LR (2012)
Clinical and laboratory changes were evaluated in rabbits after intoxication by Amorimia rigida, a plant that causes sudden death. Nine New Zealand male rabbits, averaging 3.54 kg, were categorized into three groups (n = 3) and received, for eight consecutive days, the equivalent of 30 g/kg dry matter of A. rigida water-soluble (SG) and water-insoluble (IG) extracts via nasoesophageal route. The control group received water. There were no alterations in creatine kinase enzyme (CK), CK myocardial fraction (CKMB) or troponine I (cTnI). None of the animals had clinical or electrocardiographic (conventional and Holter) alterations. There were progressive decreases in the left ventricular ejection fraction and systolic fractional shortening. Doppler echocardiography alterations suggested a systolic dysfunction in the SG and IG groups and diastolic dysfunction in IG group. It was concluded that the soluble and insoluble extracts of A. rigida cause deficit of cardiac function.